Finland in a small book. - Humphreys, Pat, ....- (Jyväskylä : Yrityskirjat, 2008)
The world is increasingly interested in Finland, its environment and society, economy and technology. Finland in a small book, now in its fourth edition, covers the issues that outsiders are curious about. An extensive index makes it an ideal reference work. Pat Humphreys has been a foreign correspondent for thirty years, covering the north of Europe for print and broadcast media in Britain, France and the United States.
Keywords: Finland -- Reisgidsen